1994
DOI: 10.1111/j.1445-2197.1994.tb02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying in Patients With Gallstone Disease With or Without Dyspepsia: Effect of Cholecystectomy

Abstract: Dyspepsia is a common complaint in patients presenting with gallstone disease. Since the stomach appears to be its site of origin, the present study was undertaken to assess gastric emptying in patients with gallstone disease and to find out its correlation with dyspeptic symptoms before and after cholecystectomy. Gastric emptying (t1/2) was prospectively assessed in 43 patients with symptomatic gallstones (29 with and 14 without dyspepsia). These data were compared with that of 20 healthy volunteers (control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…Dyspeptic symptoms might rather originate from multiple coexisting motility defects in gallstone patients, likely persisting after a cholecystectomy. This is the case in this study and in another study, which examined gallstone patients before and after a cholecystectomy . Indeed, dyspepsia persisted in a consistent number of patients.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Dyspeptic symptoms might rather originate from multiple coexisting motility defects in gallstone patients, likely persisting after a cholecystectomy. This is the case in this study and in another study, which examined gallstone patients before and after a cholecystectomy . Indeed, dyspepsia persisted in a consistent number of patients.…”
Section: Discussionsupporting
confidence: 77%
“…The extent and timing of gastric emptying worsen after gallbladder removal, pointing to the presence of altered pathways involving bile flow and/or signalling molecules. At variance with the present study, an early report found improved gastric emptying following cholecystectomy . Differences in selection and number of patients, characteristics of study design (ie two separate groups in this study vs pre‐postcholecystectomy in the study by Ibrarullah) and duration of follow‐up might account for such differences.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Seven additional publications were identified from the reference lists. Of these 34 publications 11 articles had to be excluded: in 5 the presentation of the results precluded a comparison between pre-and postoperative symptoms [5,22,27,36,39]; in 3 the subject of the article was not related to the subject under study [12,26,35]; in 1 follow-up was restricted to patients with postoperative symptoms only [16]; and the data of 2 studies had already been presented in another included study [2,18]. Thus, 23 articles were available for the analysis.…”
Section: Resultsmentioning
confidence: 99%